Comparative Study of Halal Certification Procedures in Southeast Asia and Middle Eastern Countries - Nurindra, Miura Sekar; Nurwahidin, Nurwahidin (UI Scholars Hub, 2025)
Halal certification is one of the important aspects that can promote the advancement of the halal sector worldwide. Halal certification can be used for products such as food, beverages, medicines, cosmetics, services, and others. Each country has provisions, processes, and requirements related to halal certification applications and procedures in their country. The purpose of this study is to explain the comparison of halal certification procedures in various parts of the world using case studies in Southeast Asia countries such as Indonesia and Malaysia and countries in the Middle East such as the United Arab Emirates and Turkey. This research is conducted using a qualitative methodological approach. The results of this study are that each country in Southeast Asia such as Indonesia and Malaysia and the Middle East such as the United Arab Emirates and Turkey, have their own procedures related to halal certification. These countries also have different regulations or policies, institutions, and types of halal certification but have the same goal of establishing halal certification in accordance with Islamic law. This research is expected to be a material consideration and knowledge to be completed in future studies and can be useful for the advancement of the halal industry in Indonesia.